THE PROJECT-BASED LEARNING AND ITS IMPACT ON ENGLISH PRESENTATION SKILL DEVELOPMENT - Armita Permatasari; Sri Rahayu Juniati (Institut Agama Islam Negeri Bone, 2025)
Abstract Project-Based Learning (PBL) has increasingly gained attention in English as a Foreign Language (EFL) instruction because it creates meaningful, student-centered learning experiences that support communicative competence. However, despite its recognized benefits, research focusing on the impact of PBL on the English presentation skills of non-English majors in General English classes remains limited, particularly within Indonesian private universities. To address this gap, this study aimed to examine the effect of PBL on non-English majors’ English presentation skills at Universitas Muhammadiyah Sinjai. A quasi-experimental design was employed involving a pretest–posttest control group. The experimental group was taught using PBL, while the control group received conventional instruction. An analytic rubric assessing content, organization, language accuracy, pronunciation, delivery, and use of visual aids was used to measure students’ presentation performance. The results indicated that students taught through PBL showed a significant improvement in overall presentation skills compared to those in the control group. The qualitative observations also revealed increased motivation, collaboration, and confidence among students in the PBL class. These findings suggest that PBL offers a more engaging and effective learning environment for developing presentation skills, especially for non-English majors who often have limited exposure to authentic English-speaking tasks. The study concludes that integrating PBL into General English courses can enhance students’ oral communication abilities and support more meaningful learning outcomes. Implications for teaching practice and recommendations for future research are also provided. Keywords: Project-Based Learning, Presentation Skills, English Foreign Language